Causes of Defects and Damage to Brick Masonry Elements in Historic Buildings - Niedostatkiewicz, Maciej; Majewski, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Ceramic brick masonry elements constitute the largest number of structural systems of historic buildings, especially sacral and public utility buildings. In the past, they were also very commonly used as a material for the construction of military facilities.
Keywords: masonry structures; brick; damage; mortar; monuments; reinforcement; defects; revitalization